Systematic relationships between overshooting top characteristics and anvil life cycle observed with geostationary satellites - Auth, Rachael M., author; van den Heever, Susan C., advisor; Freeman, Sean, committee member; Rasmussen, Kristen, committee member; Reising, Steven, committee member (Colorado State University. Libraries, 2026)
Deep convective storms with strong updrafts generate robust anvils and distinct cloud top structures. These structures, including overshooting tops (OTs) and above-anvil cirrus plumes (AACP), can be routinely identified atop the most powerful storms on the planet and are often indicative of severe weather, including tornadoes and large hail. The overarching goal of this study is to assess how OT characteristics are related to the structural and temporal properties of their parent anvils. Derived anvil cloud statistics from a robust database of tracked anvils and OTs using rapid scan geostationary satellite data are presented. A novel approach to identifying and tracking storm systems through their life cycle, using tobac's family tracking capabilities, was leveraged to create the database over four U.S. convective seasons. Just over 25% of nearly 61,000 identified anvils were associated with at least one OT. Analysis reveals that the mean OT lifetime was ~8.5 minutes, less than the current cadence of global full-disk geostationary satellite observations (10 minutes). OT count was found to be greatest during the mature stage of the anvil life cycle, and anvils also often overshoot for more than 20 minutes. The results shown here suggest that the most important predictors of anvil size and lifetime are OT height and count, rather than OT area or lifetime as previously hypothesized. The results also show that taller OTs are spatially larger than shallower OTs, suggesting that larger updrafts can transport more mass higher in the atmosphere. This study therefore reveals key relationships between OTs and their parent anvils and motivates future observations of updrafts and convective mass flux (CMF) from upcoming missions such as INCUS.